A managed Earth and the end of nature? - Rolston, Holmes, 1932-2025, author; JAI Press, publisher (Colorado State University. Libraries, 1999)
Humans increasingly see themselves as the planetary mangers. Perhaps nature is at an end? Natural history has been overtaken by human engineering. Others seek a revised account by which human activity is, or should be, natural. The ideal of nature, absent humans, ought to be replaced with an ideal in which the human presence is also natural. A postmodern claim is that nature always wears for us a human face. But nature neither is, or ought to be, ended. Humans belong on Earth, but nature ought also be an end in itself.
Keywords: management; nature; wildness; development; environment; war; peace; population; environmental ethics